Joint Super-Resolution Using Only One Anisotropic Low-Resolution Image per q-Space Coordinate - Golkov, Vladimir; Sperl, Jonathan I.; Menzel, Marion I.; Sprenger, Tim; Tan, Ek Tsoon; Marinelli, Luca; Hardy, Christopher J.; Haase, Axel; Cremers, Daniel (Mathematics and Visualization, 2014)
Recently, super-resolution methods for diffusion MRI capable of retrieving high-resolution diffusion-weighted images were proposed, yielding a resolution beyond the scanner hardware limitations. These techniques rely on acquiring either one isotropic or several anisotropic low-resolution versions of each diffusionweighted image. In the present work, a variational formulation of joint superresolution of all diffusion-weighted images is presented which takes advantage of interrelations between similar diffusion-weighted images. These interrelations allow to use only one anisotropic low-resolution version of each diffusion-weighted image and to retrieve its missing high-frequency components from other images which have a similar q-space coordinate but a different resolution-anisotropy orientation. An acquisition scheme that entails complementary resolution-anisotropy among neighboring q-space points is introduced. High-resolution images are recovered at reduced scan time requirements compared to state-of-the-art anisotropic superresolution methods. The introduced principles of joint super-resolution thus have the potential to further improve the performance of super-resolution methods.
CRIS-Team Scopus Importer:2023-03-08